Experiment on feeding rates of the first, third, and fifth zoae stages of the crab Hemigrapsus takanoi from Kiel fjord under different temperature and salinity levels for a period of 24 hours - Nour, Ola Mohamed; Pansch, Christian; Stumpp, Meike (PANGAEA, 2025)
Feeding rates of Hemigrapsus takanoi Zoea I , Zoea III, and Zoea V were assessed under laboratory conditions, as the number of individual Artemia spp. consumed within 24 h. Ovigerous females were collected from inner Kiel Fjord in July 2018, and reared in constant laboratory conditions. After egg hatching, larvae were reared, exposed, and held at the respective experimental treatments. Experiments were conducted on combined effect of salinity (6 levels, 10–25) and temperature (19 and 23 °C).
Keywords: Feeding rate; Hemigrapsus takanoi; Kiel Fjord; larvae